Legal nature issuance person who committed a criminal offense - Кісілюк, Е. М.; Грищук, Г. М. (Problems of legality, 2015)
The paper analyzes the legal nature of the institution issuing the person who committed the criminal offense of international and domestic law. The concept of issuing person who has committed a criminal offense in the regulatory and enforcement level.